2010
DOI: 10.2903/j.efsa.2010.1654
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety of glycerol esters of gum rosin for the proposed uses as a food additive

Abstract: The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion evaluating the safety of glycerol esters of gum rosin (GEGR) for the proposed use as a stabilising and emulsifying food additive in certain beverages to a maximum level of 100 mg/l. The Joint FAO/WHO Expert Committee on Food Additives established a group ADI of 0-25 mg/kg bw/day for glycerol esters of wood rosin (GEWR) and GEGR and tentative specifications for GEGR pending the submission of additional data. GEGR are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Therefore, the toxicological data obtained with GEWR could not be used for read across. The Panel concluded that the available data were too limited to conclude on the safety of GEGR or GETOR as food additives at the proposed uses and use levels (EFSA ANS Panel, 2010.…”
Section: Information On Existing Evaluations and Authorisationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the toxicological data obtained with GEWR could not be used for read across. The Panel concluded that the available data were too limited to conclude on the safety of GEGR or GETOR as food additives at the proposed uses and use levels (EFSA ANS Panel, 2010.…”
Section: Information On Existing Evaluations and Authorisationsmentioning
confidence: 99%
“…Analytical results on the contents of individual resin acids in GEWR measured after saponification are presented in the EFSA opinion on the safety of GEGR for the proposed use as a food additive for reasons of comparison (EFSA ANS Panel, 2010). In samples of saponificated GEWR (botanical origin not specified), the following resin acid concentrations were measured after saponification (given percentage refers to the total of each resin acid present in GEWR in bound and unbound form): abietic (19.5-26.0%), dehydroabietic (22.7-34.6%), palustric (4.29-5.90%), neoabietic (0.546-2.77%), pimaric (5.31-6.45%), isopimaric (9.35-15.0%), sandaracopimaric (5.76-6.41%) and communic (9.69-10.7%) acids (EFSA ANS panel, 2010). The given concentrations of the individual resin acids measured in GEWR samples after saponification covers the fraction of free resin acids and resin acids as hydrolysis products from esters.…”
Section: Identity Of the Substancementioning
confidence: 99%
See 1 more Smart Citation